Numerical Investigation and Optimization of Aerodynamic Effect on Solar Panels at High Altitudes in Urban Environment - P. Surendra Reddy, G. Kiran Kumar, Swapna Koneru (International Journal of Control and Automation, 2020)
Growing need of power raises the necessity of looking for sustainable energy resources to utilize the Natures free sources to consume and utilize the energy released by the sun such energy is utilized using solar panels , Growing urban culture and cities there is much greater possibilities that solar panels play an important role in power cities and buildings in this paper we attempted to study the pressure profiles and drag profiles of a traditional rectangular solar panel to overcome the dislocations and optimal placement problems. Dislocations due to air velocity and drag are the major concerns among the solar panel manufacturers. The current study deals with analyzing Aerodynamic scenarios to optimize drag and angular placement to achieve this a computational fluid dynamics study is carried out with a mathematical model where a 5 storey building is assumed to see the affect of flow past solar panel and the pressure patterns on the solar panels. Two different analysis is carried out with changing wind velocities and angles , initial angle of 0 degrees which is normal to the flow direction is solved for 5 m/s and 25 m/s wind speeds and there by changing the orientation of Panels to 45 degree inclination to investigate the Aerodynamic effects on the panels. Depending on the results obtained a futuristic Panel design will be proposed which can be optimum power generation and also aerodynamically effective.